Itinerário terapêutico de pessoas idosas com diabetes mellitus - Oliveira, Francine Feltrin de (2020)
Diabetes mellitus, a chronic non-communicable disease, requires attention in elderly people in reason of increasing the risk of functional impairment, which may directly interfere with their autonomy and independence. Faced with this context, there is the need of the elderly person with diabetes mellitus seek care in different scenarios. The model of comprehensive care for the health of the elderly proposes the connection between several points of the networks of care, involving in addition to health services, family and community, glimpsing Primary Health Care as the organizer of care. The therapeutic itinerary represents the path people take when they encounter a process of illness. In this sense, the model of Health Care System proposed by Arthur Kleinman, constituted by the popular, folkloric and professional subsystem, was used. The objective of the study was to describe the therapeutic itinerary of elderly people with diabetes mellitus registered in Family Health Strategy units in a municipality in Rio Grande do Sul. This is a qualitative study, of descriptive nature whose participants were 15 elderly people with diabetes mellitus. Data were collected through a semi-structured interview from February to April 2019. The analysis of the data was done according to the operational proposal of Minayo. The research was approved by the Committee of Ethics in Research, opinion nº 3.108.845. The results are presented in four thematic categories: correlations between the aging process and diabetes mellitus; popular practices and their implications in the care of elderly people with diabetes mellitus; perceptions of older people with diabetes about professional care; care relationships for older people with diabetes: networks woven with the support of the family and with people with close ties. From the data analysis, it was identified that the path of elderly people with diabetes is not linear, it occurs more frequently in the professional and popular care subsystem. Some elderly people scored not using the folkloric subsystem. The paths of care search are permeated by the questions of aging and focus on the trajectories that will be chosen. Questions such as physical and functional declines with compromising of the basic and instrumental activities of daily life, changes in the sexual sphere, dependence, retirement and social vulnerability were highlighted. The family was recognized as the main source of care. The Family Health Strategy was scored as the reference in care. A plurality of practices was identified with the use of teas, blessedras, faith and religiosity as a way to control and mitigate the effects of hyperglycemia. Understanding the therapeutic itineraries of elderly people with diabetes helps to clarify the paths that are followed in search of care, above all, to glimpse the cultural issues, individual and family beliefs that mobilize the elderly in this therapeutic itinerary. It is hoped that the study will allow reflections and point out ways for gerontogeriatric nursing care, and thus, offer integrals care practices to the health of the elderly population with diabetes mellitus.